Prevalence and treatment outcomes of incidental dural tears in lumbar spine surgery - Rahman, M. Mofizur; Hannan, Mohammad Abdul; Jahan, M. Sarwar; Monir, Moniruzzaman (International Journal of Research in Orthopaedics, 2025)
Background: Incidental dural tears (IDT) are common in lumbar spine surgery, varying in prevalence due to patient factors, pathology, and surgical techniques. They may cause cerebrospinal fluid leakage, headaches, and delayed recovery. Proper identification and management are essential for favorable outcomes. This study aimed to evaluate the prevalence and treatment outcomes of incidental dural tears. Methods: This study was conducted at the Department of Orthopaedics, National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR) and Sylhet M.A.G. Osmani Medical College, Sylhet, Bangladesh from January 2023 to December 2024, using purposive sampling. A total of 86 patients undergoing lumbar spine surgery were included, excluding those with infections or malignancies. Incidental dural tears and treatment outcomes were analyzed using SPSS Version 23, with significance set at p<0.05. Results: The prevalence of IDT in lumbar spine surgery was 15.1%. The IDT group consisted of 84.6% males, 23.1% patients aged ≤30 years, and 53.8% with previous spinal surgery. The IDT group had longer operation times (197.4±37.7 minutes), longer hospital stays (10.5±2.1 days), and higher drainage volumes (266.7±28.9 ml). Post-operative complications, including wound infections (23.1%) and headaches (30.8%), were more common in the IDT group. Conclusions: IDT occur in 15.1% of lumbar spine surgeries. Risk factors include male gender, younger age, and previous spinal surgery. IDT is linked to longer operation times, extended hospital stays, higher drainage volumes, and increased post-operative complications.